PENGARUH PENAMBAHAN REBUNG BETUNG DALAM PEMBUATAN NUGGET IKAN PATIN (Pangasius hypopthalamus) - Silaban, Mastrina; Herawati, Netti; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Catfish nuggets is one of the products processed using a cut of catfish relatively small and irregular then be attached to return to the product greater by adding seasoning, filler and materials fastener. This research aims to know the influence of the adding of bamboo shoots betung to quality nugget according SNI-01-6638-2002. Research methods using the complete random design consists of 4 treatments and each treatment was repeated 4 times. Treatment additions bamboo shoots begin from 0%, 10%, 20%, and 30% from 100 grams of heavy materials. The data analyzed by statistic using Anova. Organoleptic analysis with Duncan’s New Multiple Range Test (DNMRT) on 5% level. The result showed that the best treatment was the addition of bamboo shoot treatment 30%. The product has a water content of 30,22%, ash content of 1,17%, the protein content of 12,12%, 3,54% fiber content, with color are golden yellow (3,63) and color in grayish white (4,07), aroma slightly scented fish and slightly scented bamboo shoots (2,93), rather tasteless fish and a little taste of bamboo shoots (2,77), texture a bit chewy (2,73) and overall ratings between like to favorite (4,49). Keywords: catfish, betung bamboo shoots, nugget.